Faktor-Faktor Yang Memengaruhi Minat Nasabah Dalam Menggunakan Layanan Internet Banking Dengan Menggunakan UTAUT (Unified Theory Of Acceptance And Use Of Technology) (Studi Pada Pengguna Internet Banking BRI) - Sartika Amalia; Ari Kusyanti; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Internet Banking is a platform provided by each bank to facilitate its customers to make transactions without having to go to the bank directly. PT Bank Rakyat Indonesia, Tbk launched banking services that internet banking BRI in 2009. Internet Banking is one of the services offered by Bank Rakyat Indonesia so as to facilitate and launch customers in banking transactions wherever and whenever for 24 hours and can be in access through the official web of Bank Rakyat Indonesia. This research is conducted to find out what factors can influence the interest of customers in using internet banking services BRI. This study uses UTAUT (Unified Theory Of Acceptance and Use Of Technology) to know the variables Perfomance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition and Behavioral Intention. This study uses data collection techniques in questionnaire with the number of samples used between 75-100 respondents, and the number of respondents data to be analyzed by using linear regression of 100 data. The result of this research concludes that Perfomance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition have positive effect to user behavior (Behavioral Intention) in using BRI Internet Banking service.